Makna Tradisi Butale Haji di Tigo Luhah Semurup Kabupaten Kerinci - Fatonah Nurdin; Supian Supian; Denny Defrianti (Universitas Batanghari Jambi, 2021)
This study uses qualitative methods with the aim of producing qualitative data with symbolic interaction approach through the history of Butale Haji tradition and to know the meaning and value of it, in the culture of the people of Tigo Luhah Semurup, Kerinci regency. The focuses of this research were the history and the meaning of the Butale Haji traditional activities in Tigo Luhah Semurup. Understanding of the Butale Haji tradition as the symbolic interaction value in the culture of Tigo Luhah Semurup society which binds kinship and togetherness. The background of this research was starting from the interaction of the Tigo Luhah Semurup society which has been an interaction for years and has been passed down from generation to generation till present. At the time of gathering to enjoy togetherness and mutual cooperation, there was an interaction between one another among fellow citizens in joy and compassion to take their siblings to the holy land of Mecca. The results of this study indicated that the society of Tigo Luhah Semurup really maintain this Butale Haji tradition. Butale Haji tradition which was carried out consciously, with the motive and purpose of maintaining kinship, togetherness, mutual cooperation and sincerity in doing activities. Butale Haji was also as the means of communication between relatives to support each other and pray for the departure of siblings to do Hajj with happily without leave the burden and worry. In conclusion, Butale Haji traditional as the strengthening value and the adhesive friendship, togetherness, mutual cooperation, sincerity in the Tigo Luhah Semurup society in Kerinci regency.